A study on the development of tiessa (Pouteria campechiana) candy bar - Rivas, Luisa Lyn C. (1997.)
Tiessa is a nutritious fruit that is widely grown in the Philippines.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tiessa; Pouteria campechiana; Candy bar